Medical technology - Wickham, Nicholas (Belgium : Franklin Watts/Aladdin Books, 1986)
Describes technological advances in the field of medicine, including nuclear medicine, ultrasound, artificial organs, and transplant surgery.
Includes glossary and index.
Keywords: Medical technology. -- Juvenile literature; Medical innovations -- Juvenile literature